2012
DOI: 10.1007/s11060-012-0817-4
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive outcome after awake surgery for tumors in language areas

Abstract: In surgery for tumors of the dominant hemisphere, the attention devoted to quality of resection and preservation of language function has not been accompanied by comparable interest in preservation of cognitive abilities which may affect quality of life. We studied 22 patients undergoing awake surgery for glioma removal in the language areas of the brain. Besides monitoring tumor variables (size, location, histology, edema), we used a multifaceted battery of tests to investigate mood, cognition, and language i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 19 publications
7
84
1
2
Order By: Relevance
“…, Santini et al . , Satoer et al . )—all of which are abilities that could affect typing speed and, hence, writing fluency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Santini et al . , Satoer et al . )—all of which are abilities that could affect typing speed and, hence, writing fluency.…”
Section: Discussionmentioning
confidence: 99%
“…One can only speculate what factors explain the differences in typing speed found between the LGG patients and the reference group. It is known that LGG patients may present with deficits in cognitive functions such as executive functions, working memory and processing speed (e.g., Talacchi et al 2011, Santini et al 2012, Satoer et al 2012)-all of which are abilities that could affect typing speed and, hence, writing fluency. In the present study (which is part of a project focusing on effects on language ability following LGG surgery), only tests of lexical retrieval (naming and verbal word fluency) were used.…”
Section: Typing Speed Affects Writing Fluencymentioning
confidence: 99%
“…De gieter smeert een boterham -The watering-can prepares a sandwich). This task can be used for temporal cortical and subcortical areas (Bello et al, 2007;Bertani et al, 2009;Pereira et al, 2009;Santini et al, 2012). The sentences were based on BOX part 6 of Visch-Brink and Bajema (2001).…”
Section: B22 Judgment Of Semantically Anomalous and Correct Sentencesmentioning
confidence: 99%
“…Approximately one-quarter of patients with LGGs report serious problems with their neurocognitive functioning, particularly memory concentration, 34 language, and executive functions, 38,40,43,48 including at presentation. 23 Previous studies have suggested that many patients with LGG suffer from neurocognitive deficits and compromised health-related quality of life (HRQoL).…”
mentioning
confidence: 99%